Growth and no-growth boundary of clostridium perfringens in cooked cured meats – a logistic analysis and development of critical control surfaces using a solid growth medium - Ahmad, Nurul Hawa; Huang, Lihan; Hwang, Cheng An (Elsevier, 2024)
This study was conducted to evaluate the effect of sodium nitrite (NaNO2, 100–200 ppm), sodium erythorbate (SE, 0–547 ppm), sodium tripolyphosphate (STPP, 0–0.5 %), and sodium chloride (NaCl, 2–3 %) on growth of C. perfringens using a solid growth medium and to develop a growth/no-growth boundary (critical control surface, or CCS) to prevent its growth in cooked cured meat under the optimal temperature condition. Melted Shahidi Ferguson Perfringens (SFP) agar, inoculated with a 3-strain spore cocktail and mixed with NaNO2, SE, STPP, and NaCl according to a Box-Behnken response surface experimental design, was dispersed in 96-well microplates and incubated anaerobically in an incubator programmed to remain at 4 °C for 24 h, heat to 80 °C in 1.75 h, quickly (0.5 h) cool to 46 °C (optimum temperature), and then maintain at 46 °C overnight. The plates were examined optically and visually for colony formation. Any well free of growth was designated as no-growth. Logistic regression was used to analyze the growth probability (P) as affected by NaNO2, SE, STPP, and NaCl and define a CSS as meeting the criterion of P < 1/96. The results showed that STPP and the interactions of SE with NaNO2 and NaCl could reduce the growth probability of C. perfringens in SFP agar. The validation of CCS with ground beef showed an accuracy of 96.3 % for no growth of C. perfringens in the inoculated samples. The results of this study proved that cured meat can be formulated with proper combinations of NaNO2, SE, STPP, and NaCl to prevent the growth of C. perfringens even under the optimum temperature condition, thus preventing food poisoning caused by the growth of this microorganism.